Multi-Objective Microgrid Generation and Demand Response Scheduling Considering Distribution System Security - Nugraha, Candra Febri; Subekti, Lukman; Yasirroni, Muhammad (2022)
In a smart grid, the adequacy of electricity is not only determined by generation, but also by the consumer load. Demand response (DR) is one way to maintain a balance between electricity supply and load by reducing electricity consumption at certain times when necessary or when the system is stressed. However, research on the generation and DR scheduling mostly only discusses the economic impact. In this study, the economic, as well as security impact of DR, is evaluated in a microgrid operating planning. optimization is carried out to obtain the lowest generation costs while maximizing customer benefits from the DR program. The mixed-integer linear programming method is used to determine the optimal generation of each distributed generation and the optimal load reduction throughout the planning period. The results show that the consideration of DR and power flow constraints is not only able to maintain the security of the distribution system, but also results in an economical cost as compared to the scenario without DR. © 2022 IEEE.